A hexcellent chance to fall in love - Rose, Ann (Ann M.) (Berkley Romance, 2025)
"In this slightly spooky paranormal romance, will two women finally break their curse and get the happily ever after they've fought for? Each year, when no one is paying attention, The Dead of Night Halloween store appears in a new location with its giant sign and great low prices. No one sees them setting up or tearing down - one day it's just there and then, two days after Halloween, it's gone. Pepper White knows exactly how this works. For five years, ever since the last Keeper of the Store tricked her, she has been cursed - appearing when the store does, and disappearing when it goes away. People will remember The Dead of Night, but they'll completely forget Pepper. That is, until Christina Loring walks in the door. Their chemistry is instantaneous and, for the first time in five years, Pepper finds herself wishing for more time. But how do you tell the girl you're falling for that you're cursed and that you only have ten weeks together before Christina forgets . . . everything? To have a chance at happily ever after, Pepper has to do the one thing she swore she wouldn't - find the right treat to trick someone else into taking on the curse. But all's fair in love and spells, and this spooky season, Pepper and Christina are ready to stir up trouble in the name of love"--